Analgesic, anti-inflammatory and antimicrobial effects of ethanol extracts of mango leaves (Journal of the Bangladesh Agricultural University, 2011)
The present study was carried out to investigate the analgesic, anti-inflammatory, antibacterial and antifungal properties of ethanol leave extract of Mangifera indica. For evaluation of analgesic and anti-inflammatory properties, acetic acid induced writhing response model and carrageenan induced paw edema model were used in Swiss albino mice and Wistar albino rats, respectively. In both cases, leaves extract were administered and the obtained effects were compared with commercially available analgesic and anti-inflammatory drug, Diclofenac Sodium. In analgesic bioassay, oral administration of the ethanol leaves extract significantly (P